Anmeldelser - Hauge, Peter (Danish Yearbook of Musicology, 2003)
Review of: Jens Henrik Koudal (ed.): Andreas Kirchoff: Sonata a 4, Suite a 4, Sonata a 6, continuostemme ved Eilif Zachariassen, www.sheetmusicnow.com, Amazing Music World, copyright 2002.